Entitlement failure from a food quality perspective: The life and death role of vitamins and minerals in humanitarian crises - Patrick Webb; Andrew Thorne-Lyman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
The substantive role that vitamin and mineral deficiencies play in shaping crisis-related morbidity and mortality was not widely understood when Amartya Sen elaborated his arguments about moral rights of the hungry, entitlements, and public action. This chapter examines two main aspects of the `entitlement agenda' as they relate emergencies: (1) the role of micronutrients in contributing to diseases and death in humanitarian crises, and (2) knowledge and awareness of micronutrient concerns and solutions among the income-poor households most affected in emergencies. We argue that solutions to entitlement failure must operate not only at the level of prices and markets, but equally in the domains of public health and public nutrition. Entitlementsolutions focused only on food quantity, and not also on diet quality, are likely to fall short of their intended goals, and of a deeper responsibility to enhance the life-chances of survivors.
Keywords: Q18; I38; I18; 330; entitlement theory; micronutrients; food; humanitarian; emergencies; Sen